Increased Monooxygenase Activity Associated with Resistance to Permethrin in Pediculus humanus capitis (Anoplura: Pediculidae) from Argentina - Gonzalez Audino, Paola Andrea (2005)
We studied the profile of permethrin resistance in head lice populations infesting children 6-12 years old in schools and children´s homes in & around Buenos Aires, Argentina. Five permethrin resistant populations with different levels of resistance -Hogar Loyola (HL), Republica de Turquia (RT), Hogar Mitre (HM), Guardia de Honor (GH), Ricardo Guiraldes (RG)- and one susceptible population, Bandera Argentina (BA) were collected. Their level of resistance was evaluated and results showed resistance ratios (RR) of 13 for HL, 16 for RT, 22 for HM, 61 for GH and 69 for RG. In order to elucidate the possible involvement of the cytochrome P450 monooxygenase system in conferring permethrin resistance, ethoxycoumarin-O-deethylase (ECOD) activity was measured in abdomens of individual third instar nymphs and adults using a fluorometric assay.  The ECOD activity was lower in the susceptible BA population (4.7 ng/insect) than in the resistant ones (13.7 ng/insect for RG, 12.3 ng/insect for GH, 8.6 ng/insect for RT, 8.2 ng/insect for HL). ECOD activity was significantly correlated with the level of resistance in the field populations (r= 0.97, p=0.0009) suggesting a role for cytochrome monooxygenase P450 system in permethrin resistance by P. humanus capitis.